(3GdaNQjI aj eYQaI GdfjIs - (3GdMdj, CHh WGdH, aNQ GdeMbbjf, eMeO Hf MSf Hf jhSa Hf Ydj, J (B771(3g` (B1369(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg Ydi gOGjJfG HSjO GdeQSdjf (B... (3hQJHJgG Ydi aUhd, GdaUd GdChd aj MbjbI GdfjI, YQagG GdeJcdehf HCfgG EQGOI ef GdaGYd ddaYd GdebGQfI dg hGdaQb HjfgG hHjf GdYRes
(3BNQgG (B:s
(3BNQgG(B: (3hcPG GdCMGOjK GdefbhdI Ydi GdfHj hGdCFeI Ydjge GdSdGe ajeG jJYdb HGdCMcGe efgG hGLH Ydi GdcaGjI jfhj GdhLhH ajbhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 242s
(3GdPQjYI, L (B11: 160(3, L (B16: 90s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis